2021
DOI: 10.1097/gox.0000000000003720
|View full text |Cite
|
Sign up to set email alerts
|

Post-Breast Surgery Pain Syndrome: Shifting a Surgical Paradigm

Abstract: Summary: Post-mastectomy pain syndrome and the less well-described post-breast surgery pain syndrome are long-term neuropathic pain conditions that may affect more than 50% of patients after mastectomy and breast surgery. While the etiology, risk factors, and management have been reviewed in our literature, we offer here a focused outline that will gear the plastic surgeon with tools to lead a multidisciplinary, algorithmic approach to the care of patients with post-mastectomy pain syndrome/post-bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
0
12
0
2
Order By: Relevance
“…This is largely due to the regenerative properties of adipose tissue which contains adipose-derived stem cells involved in secreting pro-survival cytokines and growth factors [ 16 ]. In addition, both amitriptyline and venlafaxine, two commonly used antidepressants, have demonstrated significant effectiveness in reducing PMPS-associated pain [ 17 ]. For those who choose not to take medication or do not benefit from it, peripheral blocks offer an effective alternative [ 18 ] (Table 1 ).…”
Section: Neuromuscularmentioning
confidence: 99%
“…This is largely due to the regenerative properties of adipose tissue which contains adipose-derived stem cells involved in secreting pro-survival cytokines and growth factors [ 16 ]. In addition, both amitriptyline and venlafaxine, two commonly used antidepressants, have demonstrated significant effectiveness in reducing PMPS-associated pain [ 17 ]. For those who choose not to take medication or do not benefit from it, peripheral blocks offer an effective alternative [ 18 ] (Table 1 ).…”
Section: Neuromuscularmentioning
confidence: 99%
“…For patients with stage 1 and 2 breast cancer, postoperative pain management plays an essential role in minimizing the risk of chronic pain, collectively referred to as “persistent postmastectomy pain” [ 32 , 33 ]. To examine the status of pain management after lymph node surgery in patients with breast cancer, this study analyzed the percentage of prescriptions of pain medication according to surgery type for the preoperative period, index date, and postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports in the literature, 20-68% of breast cancer survivors suffer from some degree of PMPS [7,8]. In a Danish study by Vilholm et al, the prevalence of PMPS was reported to be 24% in 258 surgically treated breast cancer patients [9].…”
Section: Epidemiologymentioning
confidence: 99%